Sprawność indywidualnych gospodarstw rolnych w Polsce - Kapusta, Franciszek (Efficiency of Hold Agriculturale in Poland, 2005)
The paper presents results of multidimensional analysis of private farms (total 1270) which ran agricultural accounting. As this sample is not representative to all private farms, obtained results should be referred only to analysed group. Each size class of farms is well functioning, but in a different way from each other. Positives and negatives of farm size classes can be used in forming agricultural policy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 143-154